STAGES OF ECONOMIC DEVELOPMENT OF THE COUNTRY’S AGRICULTURE AND ITS INSTITUTIONAL CONDITIONS - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article describes the institutional conditions for the development of the agricultural sector in the country, the reforms carried out in agriculture and the stages of agricultural development. The article also analyzes the development of agriculture in the country using research methods. The first stage of development is the period up to the nineties of the last century, when the activities of artel, commune, chorikor, collective and state farms were carried out, the second stage is the period from 1994 to 2004, when the state’s rational policy and financial support for agricultural enterprises led to the normalization of the agricultural situation in the country, the third stage is the period of active growth from 2004 to 2017, and the fourth stage is the period of transition from raw materials to the production of finished products in agriculture (clustering), which has been ongoing since 2017. The article also analyzes the development of agriculture in stages using research methods. The first stage of development is the period up to the nineties of the last century, when the activities of artel, commune, chorikor, collective and state farms were carried out, the second stage is the period from 1994 to 2004, when the state’s rational policy and financial support for agricultural enterprises were achieved, the third stage is the period of active growth from 2004 to 2017, and the fourth stage is the period of transition from raw materials to finished products (clustering), which is being discussed in organizational, economic and regulatory legal terms.